Social Media Processing 4th National Conference, SMP 2015, Guangzhou, China, November 16-17, 2015, Proceedings - Zhang, Xichun; Sun, Maosong; Wang, Zhenyu; Huang, Xuanjing (Communications in Computer and Information Science,, 2015)
This book constitutes the thoroughly refereed papers of the 4th National Conference of Social Media Processing, SMP 2015, held in Guangzhou, China, in November 2015. The 14 revised full papers and 9 short papers presented were carefully reviewed and selected from 105 submissions. The papers address issues such as: mining social media and applications; natural language processing; data mining; information retrieval; emergent social media processing problems.